Colonization of a 'Lost World': Encrustation patterns in modern subtropical brachiopod assemblages. - Rodland, D. L.; Kowalewski, M.; Carroll, M.; Simoes, M. G. (Sepm-soc Sedimentary Geology, 2004)
The encrustation of Paleozoic rhynchonelliform brachiopods has been studied for decades, but modern brachiopods have not received similar scrutiny. The discovery of abundant subtropical brachiopods from the Southeast Brazilian Bight provides an unprecedented opportunity to assess epibiont abundance, diversity, and encrustation patterns in modern brachiopod assemblages. Across the outer shelf, encrustation frequencies vary among taxa, from mean values of 0.45% for Platidia to 9.3% for Argyrotheca. Encrustation frequencies for Bouchardia increase from 1.6% on the outer shelf to 84% on the inner shelf Larger valves are encrusted more frequently, and epibionts preferentially colonize valve interiors. Increased encrustation on the inner shelf may reflect the greater surface area of larger hosts, longer exposure of dead shells, water-mass characteristics, sedimentation rates, productivity, or other factors that vary with depth. Inner-shelf brachiopods exhibit encrustation frequencies comparable to those reported for epifaunal bivalves. The epibiont fauna is dominated by bryozoans and serpulids, with minor roles played by spirorbids, bivalves, barnacles, foraminifera, algae, and other taxa. Epibiont abundance at each site is highly variable, but sites are similar in rank importance of epibiont taxa. A different suite of epibionts colonized Paleozoic brachiopods, but similar patterns of encrustation have been observed, including preferential settlement according to valve morphology. These results provide a baseline for evaluating the encrustation of modern bivalves and ancient brachiopods, and may elucidate the macroevolutionary history of epibionts and their relationship to their hosts.